Parental Digital Literacy and Involvement in Blended Learning: A Mixed-Methods Psychological Analysis - Poursaberi, Roghayeh; Yousefpour , Nahid; Derakhshan, Noushin; Ahmadabadi, Arezoo (Applied Family Therapy Journal (AFTJ), 2026)
Objective: This study aimed to examine how parental digital literacy predicts and shapes parental involvement in blended learning environments using an integrated mixed-methods psychological approach.Methods and Materials: A convergent mixed-methods design was employed with 384 parents completing validated digital literacy and parental involvement scales, while 22 parents participated in in-depth semi-structured interviews. Quantitative data were analyzed using descriptive statistics, Pearson correlations, multiple regression, and PLS-SEM to assess predictive relationships across domains of digital literacy and involvement. Qualitative data were analyzed using reflexive thematic analysis to identify psychological processes underlying digital engagement. Results from both strands were integrated through triangulation to capture convergent and complementary patterns.Findings: Parents demonstrated moderate digital literacy, with communication and problem-solving competencies showing the strongest associations with involvement. Correlation analyses revealed robust positive relationships between all literacy domains and involvement dimensions (r = .22 to .41, p < .01). Multiple regression showed that information literacy (β = .18, p = .003), communication literacy (β = .21, p < .001), and problem-solving skills (β = .24, p < .001) significantly predicted parental involvement, explaining 43% of its variance. PLS-SEM confirmed strong paths from problem-solving to cognitive–instructional involvement (β = .24, p < .001) and behavioral supervision (β = .21, p < .001), and from communication literacy to school–home communication (β = .27, p < .001). Digital content creation and cybersecurity skills showed weaker, nonsignificant effects. Model fit indices demonstrated strong reliability (CR = .85–.91) and convergent validity (AVE = .57–.67).Conclusion: Parental digital literacy substantially influences the quality and depth of parental involvement in blended learning, with problem-solving, information handling, and communication competencies emerging as the most critical predictors. Strengthening parental digital literacy may therefore enhance home–school collaboration, support student engagement, and promote more equitable participation in blended learning ecosystems.